Endophytic Actinobacteria Associated with Dracaena cochinchinensis Lour.: Isolation, Diversity, and Their Cytotoxic Activities. (6th April 2017) - Salam, Nimaichand; Khieu, Thi-Nhan; Liu, Min-Jiao; Vu, Thu-Trang; Chu-Ky, Son; Quach, Ngoc-Tung; Phi, Quyet-Tien; Narsing Rao, Manik Prabhu; Fontana, Angélique; Sarter, Samira; Li, Wen-Jun
Abstract : Dracaena cochinchinensis Lour. is an ethnomedicinally important plant used in traditional Chinese medicine known as dragon's blood. Excessive utilization of the plant for extraction of dragon's blood had resulted in the destruction of the important niche. During a study to provide a sustainable way of utilizing the resources, the endophytic Actinobacteria associated with the plant were explored for potential utilization of their medicinal properties. Three hundred and four endophytic Actinobacteria belonging to the genera Streptomyces, Nocardiopsis, Brevibacterium, Microbacterium, Tsukamurella, Arthrobacter, Brachybacterium, Nocardia, Rhodococcus, Kocuria, Nocardioides, and Pseudonocardia were isolated from different tissues of D. cochinchinensis Lour. Of these, 17 strains having antimicrobial and anthracyclines-producing activities were further selected for screening of antifungal and cytotoxic activities against two human cancer cell lines, MCF-7 and Hep G2. Ten of these selected endophytic Actinobacteria showed antifungal activities against at least one of the fungal pathogens, of which three strains exhibited cytotoxic activities with IC50 -values ranging between 3 and 33  μ g·mL −1 . Frequencies for the presence of biosynthetic genes, polyketide synthase- (PKS-) I, PKS-II, and nonribosomal peptide synthetase (NRPS) among these 17 selected bioactive Actinobacteria were 29.4%, 70.6%, and 23.5%, respectively. The results indicated that the medicinal plant D. cochinchinensis Lour. is a good niche of biologically important metabolites-producing Actinobacteria.